NO LAUGHING MATTER. Issue 12 (15th November 2016) - Jones, Lliwen; Thomas, Rhys; Peall, Kathryn; Massey, Thomas; Moat, Stuart; Corkill, Robin; Pickersgill, Trevor
Abstract : A 36-year-old man presented with three weeks of unsteadiness and tingling extremities. Examination showed increased lower limb tone, profound loss of vibration and proprioception sense, and ataxia. Six months later, his 33-year-old brother presented with similar symptoms. His examination showed pseudoathetosis, suppressed reflexes and ataxia. Both were amnestic with ACE-R scores of 86 and 84. Investigations were similar in both cases: markedly low vitamin B12 levels (92 ng/l, 109 ng/l), raised lactate dehydrogenase and methylmalonic acid concentrations, longitudinally extensive increased signal in the cervical/thoracic spinal cord on T2 weighted MRI, and sensorimotor axonopathy on neurophysiology. One patient had a markedly raised serum homocysteine level. On direct questioning the first brother described a heavy nitrous oxide habit, consuming 7200 cartridges over six weeks. The other consumed up to 600 cartridges of nitrous oxide per day for two weeks. A diagnosis was made of subacute combined degeneration of the cord and sensorimotor neuropathy secondary to B12 deficiency provoked by nitrous oxide misuse. Their symptoms improved with parenteral B12 replacement and cessation of nitrous oxide use. We report two brothers with neurological sequelae from nitrous oxide abuse, illustrating the importance of a thorough family and recreational drug history.